New Headway English Course : Pre-Intermediate Workbook With Key - Soars, John and Soars, Liz (Oxford, New York Oxford University Press, 2009)
A new edition with a modified syllabus and extensive new material.
Include Illustration
Keywords: English language -- English language--Pronunciation -- English language--Study and teaching--Foreign speakers